Bench Grafting in Custard Apple (Annona squamosa L.) as Influenced by Scion Thickness and Time of Grafting - Kumar, Sunil; Shukla, A.K. (Indian Journal of Agroforestry, 2020)
An experiment on bench grafting in custard apple (Annona squamosa L.) employing cleft grafting technique was conducted at Indian Grassland and Fodder Research Institute, Jhansi during 2007. Bare rooted stocks of custard apple having 0.6 cm diameter were bench grafted with dormant scion of cv. Balanagar. Dormant scion shoots having 0.6 cm thickness used for grafting has given highest graft success (96.4%) when it was performed on 29th May, where as minimum (37.8%) recorded when 0.8 cm thick scion was grafted on 6th June. Days taken to sprouting, length of sprout, collar diameter, number of secondary branches and number of secondary roots per plant were significantly influenced by scion thickness and time of grafting.